2015
DOI: 10.1039/c4cc09355k
|View full text |Cite
|
Sign up to set email alerts
|

Transforming chitosan into N-doped graphitic carbon electrocatalysts

Abstract: Chitosan, the only alkaline polysaccharide in nature with rich nitrogen content, is used as the sole precursor to obtain N-doped graphitic carbon-based ORR electrocatalysts. The findings of this work demonstrate that cheap, plentiful and renewable biomasses can be transformed into high value functional carbon materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 29 publications
1
63
0
Order By: Relevance
“…The peaks appearing at 25° and 44° correspond to (002) and (100) reflections of graphitic carbon, respectively. 6 It has been reported that the degradation of APP at above 200 ˚C results in a highly condensed polyphosphoric acid and the azeotropic P 4 O 10 -H 2 O mixture boils above 600 ˚C. 14 Therefore, we infer that the interface between the liquid of P 4 O 10 -H 2 O and the melt PDA lead to the graphene-like sheets.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The peaks appearing at 25° and 44° correspond to (002) and (100) reflections of graphitic carbon, respectively. 6 It has been reported that the degradation of APP at above 200 ˚C results in a highly condensed polyphosphoric acid and the azeotropic P 4 O 10 -H 2 O mixture boils above 600 ˚C. 14 Therefore, we infer that the interface between the liquid of P 4 O 10 -H 2 O and the melt PDA lead to the graphene-like sheets.…”
mentioning
confidence: 76%
“…4 The adsorbed O 2 molecules have weaker bond energy, which is beneficial to reduce the activation energy of the ORR. 5 Moreover, some studies reveal that the ORR catalytic activity can be further enhanced by co-doping carbon with S-N, 6 B-N, 7 and P-N 8 etc.…”
mentioning
confidence: 99%
“…Platinum based materials are efficient ORR catalysts but the large-scale commercial use is limited mainly due to its prohibitive cost and scarcity as well as the sensitivity to time dependent drift and CO deactivation [12][13][14]. Therefore increasing amount of efforts have been directed to develop cost-effective alternatives such as metal-free or non-precious metal based counterparts to replace commercial platinum catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, nitrogen-doped carbon electrocatalysts are usually fabricated using expensive carbon sources and labor-intensive post-doping 17,18 , which consequently increase the cost and unavoidably cause ununiformed doping or damage to the synthesized carbon structures 19 . What's worse, the pyrolysis of common carbon sources usually result in non-porous and low graphitized materials (low surface area/pore volume and low conductivity) due to the absence of template effect and metal catalysis, respectively 20,21 .…”
Section: Introductionmentioning
confidence: 99%